PELAKSANAAN PENYIDIKAN TINDAK PIDANA JUDI ONLINE BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DI WILAYAH HUKUM POLISI RESOR KOTA PEKANBARU - Frontya Moren Westy; Mukhlis Ridwan; Erdiansyah * (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
ABSTRACTCriminal online gambling there were many now. Cases of criminal acts onlinegambling in the City Pekanbaru was caused many people want to find opportunities to meettheir basic needs. But with no possible needs are met with many people to do the things thatare against the rule of law , affecting negative impact on public order and security of thecommunity. I'm interested in doing research with the title of an investigation of a CriminalAct Online gambling Based on Act No. 11/2008 about Information and ElectronicTransaction in Law Region Police Resort City of Pekanbaru . In this final project will bediscussed about the issue of How An investigation of a Criminal Act Online gambling Basedon Act No. 11/2008 about Information and Electronic Transaction in Law Region PoliceResort City of Pekanbaru . What are the inhibiting factors which occurred in An investigationof a Criminal Act Online gambling Based on Act No. 11/2008 about Information andElectronic Transaction in Law Region Police Resort City of Pekanbaru . Whatever effortsto address the obstacles to An investigation of a Criminal Act Online gambling Based on ActNo. 11/2008 about Information and Electronic Transaction in Law Region Police Resort Cityof Pekanbaru .Conclusion is that An investigation of a Criminal Act Online gambling Basedon Act No. 11/2008 about Information and Electronic Transaction in Law Region PoliceResort City of Pekanbaru not yet walked with maximum .The rule of law that less firm, stilllack of coordination between law enforcement agencies, the limited human resources theinvestigator, less facilities and infrastructure law enforcement agencies. Efforts to solveobstacles that arise in the execution is the rule of law firm , to improve coordination betweenlaw enforcement agencies, improve the ability to the police, improve infrastructure in lawenforcement.Key words : Criminal –Investigation-Online Gambling